Comparative study of detection of diabetic neuropathy by clinical and nerve conduction study in type 2 diabetes mellitus patients - Mohan, Gurinder; Chandey, Manish; Monga, Anusha; Dev, Parik (International Journal of Advances in Medicine, 2018)
Background: Diabetes mellitus is known for its complications such as retinopathy, neuropathy and nephropathy. Diabetic neuropathy is one of the devastating complication associated with diabetes mellitus. The objective of this study was to detect sensory motor neuropathy in type 2 Diabetes mellitus by clinical examination and nerve conduction study and to correlate clinical features of peripheral neuropathy with nerve conduction study in Type 2 Diabetes mellitus. Methods: This study was undertaken to study types of neuropathy in type 2 diabetes and to correlate clinical features of peripheral neuropathy with nerve conduction study in type 2 diabetes mellitus.100 patients with diabetes whose onset of diabetes mellitus after age of 30 years and duration of diabetes 5 years or more visiting SGRDIMSR, Vallah, Amritsar were subjected to nerve conduction study to find out peripheral neuropathy. Results: Eight four percentage patients were found to have neuropathy on NCS whereas only 61% of patients were found to have neuropathy on clinical examination and detection rate with NCS was statistically significant (p <0.001) as compared to clinical examination. Conclusions: NCS helps in early detection of neuropathy and most common form of diabetic neuropathy is distal symmetrical polyneuropathy.